Q: What is the answer to x2 times 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 * -3x = -3x3

x2-3x-28

Hmm - you need to phrase your question a little better. Which of these are you looking for? x2 - 3x + 2x - 2 = x2 - x - 2 = (x - 2)(x + 1) x2 - (3x + 2)(x - 2) = x2 - 3x2 + 6x - 2x + 4 = -2x2 + 4x + 4 = -2(x2 - 2x - 2) x2 - 3x + 2(x - 2) = x2 + x - 4

(x2+3x-4) (x-4)

If you mean: x2+3x+2 then it is (x+1)(x+2) when factored

Related questions

3x

x2 * -3x = -3x3

x2-3x-28

Hmm - you need to phrase your question a little better. Which of these are you looking for? x2 - 3x + 2x - 2 = x2 - x - 2 = (x - 2)(x + 1) x2 - (3x + 2)(x - 2) = x2 - 3x2 + 6x - 2x + 4 = -2x2 + 4x + 4 = -2(x2 - 2x - 2) x2 - 3x + 2(x - 2) = x2 + x - 4

If you mean x2-3x+5 then the answer is none because its discriminant is less than zero

x2 - 3x + 2 = 0

The expression x2 + 3x +8 is a quadratic trinomial.

(x2+3x-4) (x-4)

3 - 3x + x2 - x3 = (1 - x)(x2 + 3)

x3 + x2 - 3x - 3 x(x2 + x - 3) - 3

(x2 + 3x + 5)(x2 - 3x + 4)

x2 - 3X - 10 = (X - 5)(X + 2)So, (X2 - 3X -10) / (X-5) = X + 2